Investigating the effect of location, specifically shopping centres, on franchisees' entrepreneurial orientation: A cluster analysis - M. Botha; T. Prawlall (South African Journal of Business Management, 2017)
Franchisees play an important role in franchise systems, as they are responsible for managing their business and ensuring its overall performance. Since earlier research confirmed the relationship between entrepreneurial orientation (EO) and performance, this study explores the effect of location on the five dimensions of EO for franchisees. This study assessed franchisees, their risk taking, innovation, pro-activeness, competitive aggression and autonomy, and investigated location clusters related to this. Location was investigated from a geographical and operational stance. A face-to-face survey was conducted among 104 franchisees operating in four major cities in the retail sector in South Africa. Two clusters were identified: `operating inside of shopping centres' (50%) and `operating outside of shopping centres' (50%). Contradictory to what was found in the literature, the results indicate that a franchisee is likely to be more entrepreneurially orientated when operating outside of a shopping mall in the Johannesburg region. The strongest and weakest EO dimensions in terms of cluster construction were identified. Furthermore we found that, since the EO dimensions are highly correlated, it is likely that a franchisee will experience high levels of all of the dimensions simultaneously and therefore share in the positively associated benefits of EO, such as growth and performance.
Keywords: 650